NATURE AS INSPIRATION IN THE ART OF ARTIST VINCENT VANGOGH - Renu,; Sonika, (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Vincent Van Gogh, the renowned Western artist born in the Netherlands, was a unique talent with a nature-loving personality. Nature has influenced humanity in every sphere, which various artists have presented to the world through their works, such as poets in poetry, writers in articles, musicians in music, and painters in their paintings. According to Vincent, "If you truly love nature, you will find beauty everywhere." Vincent Van Gogh presented his perspective on nature through his works. He was an introverted personality since childhood, which deepened his connection with nature. He had a system of communication with trees, plants, flowers, mountains, and birds. Vincent's mind was always restless and filled with detachment. In this world, he became absorbed in nature in search of his goal, where he found peace and solace. Vincent captured every moment of nature's light and color on his canvas instantly, even capturing the wind in the bushes and wheat waves, leaving the audience amazed. He was an artist who didn't worry about his physical well-being but was more concerned with capturing every moment of nature. Having colors, canvas, and brushes was enough for him, even without food. The scorching sun rays couldn't stop him from painting, but due to various reasons, Vincent's physical and mental health began to deteriorate. Despite this, he didn't abandon painting; instead, he merged his inner state with nature and created masterpieces. This unconquerable spirit is what has given him an indelible image in the world.